Influência dos agregados reciclados nas propriedades reológicas e mecânicas do concreto autoadensável - Campos, Renan Serralvo [UNESP]; Barbosa, Mônica Pinto; Pimentel, Lia Lorena; Maciel, Geraldo de Freitas [UNESP] (FapUNIFESP (SciELO), 2018)
Recycling of mineral fraction of construction and demolition wastes (CDW), in form of aggregates, is seen as an alternative to reduce environmental impacts caused by construction. Recycled aggregates present higher water absorption and lower mechanical resistance and density when compared to natural ones, which will influence the properties of the produced concretes. The aim of this study was to investigate the influence of recycled aggregates in the rheological and mechanical properties of self-compacting concrete (SCC). For this, four distinct compositions of SCC were analyzed, one of them being produced only with natural aggregates. The other mixtures used fine and/or coarse recycled aggregates instead of natural aggregates, at 20% by mass. It was also carried out the rheological characterization of cement paste and mortars destined to SCC production, through rotational rheometry. The rheological characterization of pastes, mortars and concretes is a way to evaluate the behavior of these composites in fresh state, providing useful information that will aid in mix design process and quality control. The properties of fresh concrete were evaluated in terms of slump-flow test, t500 and V-funnel time, passing ability and segregation resistance. In hardened state, compressive strength, splitting tensile strength and static modulus of elasticity of concretes were determined. Through the obtained results it was possible to verify the loss of fluidity in mortars and concretes that used recycled aggregates. On the other hand, there was no significant reduction in the mechanical properties of concretes produced with 20% of coarse or fine recycled aggregates.
Influence of recycled aggregates on rheological and mechanical properties of self-compacting concrete
Keywords: Construction and demolition waste; Recycled aggregates; Rheology; Self-compacting concrete